Evaluating a solvent extraction process route incorporating nickel preloading of Cyanex 272 for the removal of cobalt and iron from nickel sulphate solutions - Olivier, M.; Dorfling, C.; Eksteen, Jacques (Elsevier, 2012)
Crude nickel sulphate solutions are produced during the first stage leach of Platinum Group Metal (PGM) containing converter matte in a Sherrit® atmospheric matte leach process. Iron and cobalt sulphates contaminate the nickel sulphate stream due to dissolution during the matte leach process. While iron is an unwanted contaminant, cobalt sulphate production presents a potentially valuable by-product, as long as removal of these metal ions does not introduce other forms of contamination into the solution. Experimental work was performed to evaluate the removal of 1 g/l cobalt and 3 g/l iron from a sulphuric acid leach solution containing 80 g/l nickel using solvent extraction with Ni-Cyanex 272. The effects of various process parameters on preloading, extraction, and stripping were investigated. Based on full factorial experimental designs, the parameters with the largest effects on the process performance were determined to be pH and organic/aqueous (O/A) ratio for preloading, nickel loading and O/A ratio for extraction, and H2SO4 concentration and O/A ratio for stripping.These variables were evaluated in further batch experiments to determine conditions that would allow the production of a high purity nickel sulphate solution and selective stripping of cobalt and iron from the organic phase, and the batch tests results were validated by performing continuous tests on a laboratory scale mixer-settler setup. A flow sheet that allows the production of refined nickel sulphate and cobalt sulphate solutions by extraction with nickel preloaded Cyanex 272 and selective stripping has been proposed. Regeneration of the organic phase is achieved by stripping with 1 M sulphuric acid, which yields an iron containing aqueous stream as effluent.